2016
DOI: 10.1016/j.ijggc.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic assessment of CO 2 quality effect on its storage and transport: CO 2 QUEST

Abstract: This paper provides an overview of the aims, objectives and the main findings of the CO 2 QUEST FP7 collaborative project, funded by the European Commission designed to address the fundamentally important and urgent issues regarding the impact of the typical impurities in CO 2 streams captured from fossil fuel power plants and other CO 2 intensive industries on its safe and economic pipeline transportation and storage. The main features and results recorded from some of the unique test facilities constructed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“… Even though high purity CO2 (>95%) is normally targeted after CO2 capture, different types and levels of impurities may be present in the CO2 to be transported and stored. Although these impurities may only be present in small amounts, several studies have shown that the potential associated impurities can have a significant impact on design and cost of CO2 conditioning, transport, and storage [116,117,134,135]. However, this impact will however depend on the types and levels of impurities present in the CO2 stream and thus the combination of industrial plant, CO2 capture technology considered and targeted CO2 specifications for storage or use [136].…”
Section: Flue-gas Treatment Requirementsmentioning
confidence: 99%
“… Even though high purity CO2 (>95%) is normally targeted after CO2 capture, different types and levels of impurities may be present in the CO2 to be transported and stored. Although these impurities may only be present in small amounts, several studies have shown that the potential associated impurities can have a significant impact on design and cost of CO2 conditioning, transport, and storage [116,117,134,135]. However, this impact will however depend on the types and levels of impurities present in the CO2 stream and thus the combination of industrial plant, CO2 capture technology considered and targeted CO2 specifications for storage or use [136].…”
Section: Flue-gas Treatment Requirementsmentioning
confidence: 99%
“…Further, to be a low-cost and easily deployed tracer, CH 4 must be present in the captured CO 2 stream, thereby avoiding the cost and potential environmental risks associated with adding a tracer. CH 4 is a common constituent of pre-combustion CO 2 capture from coal or biomass; CO 2 streams from these sources typically contain ~100 ppmv CO 2 Porter et al, 2016(Porter et al, 2016. However, depending on the specifics of the capture process itself, the CH 4 may be present in <1 ppmv concentrations (Porter et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pipeline-based transport has traditionally been regarded as the preferred means of transport due to its low cost of transport for large capacities and low-to-medium-distances. As a result, many research efforts have focused on a wide range of aspects of pipelinerelated infrastructures: Fundamentals [13], safety [14,15], design and cost [16][17][18][19], the impact of impurities [20,21], and network deployment [11,22,23]. However, the past decade has seen a growing interest in tank-based transport of CO 2 and in the use of ships in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al [39] have shown that transport pressures above 20 barg are not cost-competitive, but their study lead to estimates similar to the pressure range of key interest (7-15 barg) to be conclusive. Furthermore, the effect of potential impurities in the CO 2 stream after capture on design and costs of CO 2 shipping has received very little consideration, although several studies [21,39] have shown significant impact in the case of pipeline-based transport. In the present study, we thus focus on an in-depth techno-economic comparison of the two most relevant transport pressures (7 and 15 barg) [25,[40][41][42] taking into account the many parameters that can affect such a comparison, including annual transport volumes, transport distance, the impact of impurities, purity requirements, key uncertainties, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation